Romantic Love and Intimacy Experiences: Discourses of Immigrant Women In Portugal - Silva, Estefânia (2022)
Based on a critical feminist framework, this paper describes qualitative research that aims to understand how immigration influences women’s experiences of love and intimacy. Eight immigrant women with an average age of 32.25 years old were interviewed, and the subsequent data were analysed using a critical discourse analysis methodology. The results reveal how women’s experiences of love and intimacy are marked by cultural standards informed by gender norms, and these lead to power imbalances in several aspects of their lives. Intimate relationships are particularly affected by social representations from the country of origin, with more conservative political systems predicting more conservative experiences of love and intimacy.